Immunomodulatory activities of extracts of Caesalpinia pulcherrima. Issue 3 (3rd July 2018) - Khan, Fouzia; Dastagir, Nida; Lateef, Mehreen; Yousuf, Muhammad; Mirani, Zulfiqar Ali; Mesaik, Ahmed; Faizi, Shaheen; Kazmi, Shahana Urooj
ABSTRACT: The anti-inflammatory potential of extracts of all parts of Caesalpinia pulcherrima and fractions of fresh pods were explored. Each part of C. pulcherrima was extracted with methanol, acetone, and water. Fresh pods were further processed for fractionation. Methanol extract of pods (CP-Pods-M, 292 g) was subjected to solvent–solvent separation, which gave hexane (PE), ethyl acetate (EA), butanol (BUT), and aqueous (AQ) phases separately. EA phase (EA INSOLUBLE) was washed with water (EA AQ WASH) and dried with anhydrous Na2 SO4 then treated with charcoal. It was further filtered and termed as EA 1 + 2 and EA 1. Hexane (P.E) phase was evaporated to give fraction PE 1 + 2. Aqueous phase provided aqueous fractions (AF) and the residue left after freeze-drying was termed as aqueous deposit (AD). The effect of all extracts of the plant and fractions of fresh pods were studied for oxidative burst activity of whole blood phagocytes, neutrophils, and murine macrophages J 774.2 by using chemiluminescence technique. Antioxidant potential was also evaluated by DPPH radical scavenging assays. Inhibition on reactive oxygen species (ROS) production of whole blood phagocytes was observed with IC50 values ranging between 1.6 ± 0.78–8.0 ± 0.8 µg mL −1, which was lower than the standard ibuprofen as assessed by methanolic extracts of fresh fruit and flower, acetone and aqueous extracts of dry fruits and their coat, aqueous and acetone extracts of fresh fruit and their coat. The fractions EA INSOLUBLE, EA AQ WASH, EA 1 + 2, PE 1 + 2, AF, AD, and EA 1 exhibited inhibition on ROS by whole blood cells, IC50 values ranges (1.62–9.18 µg mL −1 ). Extracts of the plant and fractions from fresh pods also inhibited intracellular and extracellular ROS production in the isolated human neutrophils and murine macrophage cells J774.2.